2017
DOI: 10.2134/jeq2016.07.0274
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Losses during Winter and Summer Storage of Separated and Unseparated Digested Cattle Slurry

Abstract: Management factors affect nutrient loss during animal manure slurry storage in different ways. We conducted a pilot-scale study to evaluate carbon (C) and nitrogen (N) losses from unseparated and digested dairy slurry during winter and summer storage. In addition to season, treatments included mechanical separation of digestate into liquid and solid fractions and bimonthly mixing. Chemical analyses were performed every 2 wk for the mixed materials and at the start and end of storage for unmixed materials. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
0
3
0
3
Order By: Relevance
“…These nutrients have agronomic values and are present in the undigested fraction from the AD process, which is known as digestate (Nkoa, 2014). Despite the agronomic value of the digestate its storage, processing, and application to farmland are often associated with environmental concerns such as ammonia emission and nutrient leaching particular after land application (Perazzolo et al, 2017;Perazzolo et al, 2016). The traditional approach such as dewatering and drying are extensively used to manage AD digestate even though this contributes to ammonia emission and nutrient depletion (Pantelopoulos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These nutrients have agronomic values and are present in the undigested fraction from the AD process, which is known as digestate (Nkoa, 2014). Despite the agronomic value of the digestate its storage, processing, and application to farmland are often associated with environmental concerns such as ammonia emission and nutrient leaching particular after land application (Perazzolo et al, 2017;Perazzolo et al, 2016). The traditional approach such as dewatering and drying are extensively used to manage AD digestate even though this contributes to ammonia emission and nutrient depletion (Pantelopoulos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature showed a positive relationship with NH 3 -N emissions from slurry storage (Figure 1c), but the relationship was only significant at a 0.1 significance level. Previous studies also demonstrated that the N loss from slurry storage in summer (average air temperature 21.4 • C) was much greater than storage in winter (average air temperature 6.5 • C) [41]. Ammonia release from a slurry storage tank is a combination of diffusion and convective movements over the slurry surface, which could be parameterized by the dissociation constant and the overall mass transfer coefficient [31,42,43].…”
Section: Temperaturementioning
confidence: 99%
“…At present, the volume of biogas slurry produced by biogas projects in China has exceeded 1 billion tons each year [ 4 , 5 ]. Biogas slurry may cause serious pollution to the soil and groundwater if not disposed of in time, due to the high organic content and poor biodegradability [ 6 ]. The application of biogas slurry to farmland is seasonal, while the biogas slurry produced by biogas projects is uninterrupted.…”
Section: Introductionmentioning
confidence: 99%